EXPLORING THE ETHNOMATHEMATICS IN PHILIPPINE FOLKLORE: THE LEGEND OF BAKUNAWA - Gabica, Dexter G. (Ethnomath Association in cooperation with Universitas Negeri Yogyakarta, 2025)
This study explores the Legend of Bakunawa through the lens of ethnomathematics, examining how indigenous Filipino folklore encodes mathematical concepts. Using Bishop’s six universal mathematical activities—counting, locating, measuring, designing, playing, and explaining—the research identifies culturally embedded forms of mathematical thinking within the narrative. The legend, which tells of a serpent-like dragon attempting to devour the seven moons, contains patterns, sequences, spatial reasoning, and symbolic numeration that align with core mathematical principles. Through qualitative analysis and ethnographic context, the study highlights how storytelling functions as both a cultural and educational tool, bridging oral tradition and formal mathematics education. The findings affirm that the Bakunawa myth, like many indigenous narratives, provides a culturally rich and pedagogically sound foundation for teaching mathematical concepts. These stories are vessels of mathematical knowledge, which help educators promote culturally responsive pedagogy, strengthen learner identity, and enrich classroom engagement.